THE VALUE OF INTERLEUKIN-12B (P40) GENE PROMOTER POLYMORPHISM IN PATIENTS WITH SCHIZOPHRENIA IN A REGION OF EAST TURKEY - Ozbey, Ulku; Tug, Esra; Kara, Murat; Namli, Mustafa (Wiley-Blackwell, 2009)
[Abstract Not Available]